WORD OF MOUTH, CUSTOMER EXPERIENCE AND INNOVATION ON REPURCHASE INTEREST (Study on Shopee Customers at Singosaren Plaza Surakarta) - Ida Aryati Dyah; Sinta Sukmawati; Endah Kristiyani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this study was to determine the effect of repurchase intention in terms of word of mouth, customer experience and innovation (a study on shopee customers at Singosaren Plaza Surakarta). Total population of this study 170 people, the number of samples of this study 118 respondents. A questionnaire with a Likert scale as a measuring tool is the data collection method used in this study. The analytical tools used are Multiple Linear Regression, F Test, t Test, and the Coefficient of Determination. Based on the results obtained in this study, the most dominant variable is the customer experience variable. Based on the results obtained in this study that there is a simultaneous and partial influence between word of mouth. Keywords: Repurchase Intention, Word of Mouth, Customer Experience, and Innovation